Clinically oriented anatomy - Moore, Keith L.; Agur, Anne M. R.; Dalley, Arthur F. (Lippincott Williams & Wilkins, 2010)
Provides first-year medical and allied health students with the clinically oriented anatomical information that they need in study and practice. This textbook offers comprehensive coverage of anatomy, presented as it relates to the practice of medicine, dentistry, and physical therapy